Evolución de la auditoría de Sistemas en la era digital - Sánchez Hernández, Manuel Eduardo; Robles Bolívar, Catherine Paola (Universidad Antonio Nariño, 2024)
This academic article examines the evolution of systems auditing in response to technological advances and the increasing complexity of computer systems. The technological transformations that promoted the transition to the digital era and their impact on the management and security of computer systems are highlighted. The critical role of systems auditing in ensuring cybersecurity, data protection and regulatory compliance in a highly interconnected digital context is analyzed. Additionally, key recommendations for system auditing are provided in relation to emerging technologies such as quantum computers.